KOMUNIKASI DAN OPTIMALISASI BRANDING PARIWISATA BERKELANJUTAN DI SERIBU BATU SONGGO LANGIT YOGYAKARTA - Dyaloka Puspita Ningrum (Institute of Research and Community Outreach - Petra Christian University, 2022)
Various campaigns for the rise of the tourism sector are intensified almost every time, including at the Thousand Stones Songgo Langit tourist attraction, Yogyakarta. By using destination branding theory, this research aims to explore the ins and outs of what has been done, is being done or will be done by the tour operator to further strengthen the brand and quality of the destinations offered. The communication aspect is no less important as a focus for measuring the achievement of the concept of sustainable tourism in the current era because it has a significant impact on current and future conditions. Especially in the midst of serious competition that organizers must face, so that in this case, activities related to promotion, publication and branding of a tourist destination must be packaged in such a way. By using descriptive qualitative method, the results of the study show that there is a unique brand that is indirectly successfully created by visitors at that location. However, various marketing strategies and tactics that have been carried out previously still need to be improved again. The sustainable tourism development program with all its benefits really balances the ecosystem. So that in the future, more cooperative cooperation from all levels of stakeholders is needed.